Phenolic compounds and antioxidant activity in red fruits produced in organic farming. - Guiné, Raquel (2014)
In this work were studied three red fruits (raspberry, gooseberry and blueberry) produced in organic mode, to evaluate the variations in the content of phenolic compounds and antioxidant capacity along maturation. The phenols were extracted from the fruits with two solvents (methanol and acetone) and were quantified by the Folin-Ciocalteu method. The antioxidant activity was determined with two methods (HPPH and ABTS). Furthermore, HPLC was used to identify and quantify some phenolic compounds present in the fruits analyzed. The results showed that the total phenolic compounds in all fruits decreased along maturation, either in the methanol or acetone extracts (23 % and 20 % reduction, on average, for methanol and acetone extracts, respectively), although in methanol extracts the levels of phenolic compounds were always higher (0.54 and 0.21 mg GAE/g). The blueberry showed higher level of total phenolics in methanol extract (average 0.67 mg GAE/g), while in the acetone extract it was gooseberry (average 0.31 mg GAE/g). At the end of maturation, all fruits studied had similar values of antioxidant capacity as determined by DPPH method (0.52 mmol Trolox/g). For the ABTS method, blueberries showed higher values of antioxidant activity (6.01 mmol Trolox/g against 3.01 and 2.66 mmol Trolox/g, for raspberry and gooseberry, respectively). Furthermore, the HPLC analysis allowed to identify monomeric anthocyanins and phenolic acids in the three fruits studied.